2004
DOI: 10.1007/s11151-004-1972-3
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Survival of Spanish Manufacturing Firms

Abstract: This paper analyses the factors determining Spanish manufacturing firms’ survival–and exit. The data are drawn from the survey Encuesta sobre Estrategias Empresariales for the period 1990–1999. The methodology includes both non-parametric techniques and the estimation of a Cox proportional hazards model (CPHM). Our results suggest that the probability of exit is higher for small firms and also for young and mature firms. Furthermore, exporting firms and firms performing R&D activities enjoy better survival pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(82 citation statements)
references
References 52 publications
2
72
1
7
Order By: Relevance
“…This result is not consistent with the obtained by Quirós and Lisboa (2014) and Pérez et al (2004). However, due to the significant interaction effect present, the individual results must be controlled for the effects of the other predictor.…”
Section: Resultscontrasting
confidence: 93%
“…This result is not consistent with the obtained by Quirós and Lisboa (2014) and Pérez et al (2004). However, due to the significant interaction effect present, the individual results must be controlled for the effects of the other predictor.…”
Section: Resultscontrasting
confidence: 93%
“…Many previous studies have suggested that there is a positive relationship between plant size and survival (see, for example, Audretsch and Mahmood (1995), McCloughan and Stone (1998), Disney et al (2003), Perez et al (2004) and Persson (2005)). The main explanation put forward for this relationship relates to the view that larger firms are more likely to have levels of output close Industry-specific variables have been widely examined in previous work in this area.…”
Section: Variablesmentioning
confidence: 98%
“…Smallness tends to increase firm exits (Grilli et al, 2010;Pérez et al, 2004), since firms entering the market on a relatively small scale may face cost disadvantages and greater difficulties in accessing capital and labor markets compared with wellestablished firms. However, we still know little about the survival patterns of firms during a crisis period.…”
Section: Introductionmentioning
confidence: 99%